Bank Tax in the European Union - Piotr MASIUKIEWICZ; Pawel DEC (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2011)
The imposition of bank tax is being discussed both in the Europe and the USA. A number of countries have already introduced this tax. However, the opinions of different countries on the issue are diversified. In this connection, the imposition of uniform bank tax within the European Union seems doubtful. And this is the thesis of article. Legislating this special property tax poses a number of questions: (a) is it a legitimate anti-crisis instrument? (b) why is the growth in value within the banking sector limited through a number of financial levies, while there are no burdens of this kind in other financial and non-financial sector? (c) what is being planned in EU and individual member states in this area.